The future of starch bioengineering: GM microorganisms or GM plants? - Hebelstrup, Kim H.; Sagnelli, Domenico; Blennow, Andreas (Frontiers in Plant Science, 2015)
Plant starches regularly require extensive modification to permit subsequent applications. Such processing is usually done by the use of chemical and/or physical treatments. The use of recombinant enzymes produced by large-scale fermentation of GM microorganisms is increasingly used in starch processing and modification, sometimes as an alternative to chemical or physical treatments. However, as a means to impart the modifications as early as possible in the starch production chain, similar recombinant enzymes may also be expressed in planta in the developing starch storage organ such as in roots, tubers and cereal grains to provide a GM crop as an alternative to the use of enzymes from GM microorganisms. We here discuss these techniques in relation to important structural features and modifications of starches such as: starch phosphorylation, starch hydrolysis, chain transfer/branching and novel concepts of hybrid starch-based polysaccharides. In planta starch bioengineering is generally challenged by yield penalties and inefficient production of the desired product. However in some situations, GM crops for starch bioengineering without deleterious effects have been achieved.